2010
DOI: 10.1111/j.1365-2605.2009.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine induces ram sperm hyperactivation independent of cAMP‐dependent protein kinase

Abstract: We have previously shown that a cocktail-containing phosphodiesterase inhibitors (theophylline and caffeine), a phosphatase inhibitor (okadaic acid) and dibutyryl-cAMP promoted specific protein tyrosine phosphorylation in ram spermatozoa during incubation in capacitating conditions. Here, we show, for the first time, that this cocktail induced a progressive time-dependent increase in the capacitated-sperm subpopulation. The addition of either the analogue of adenosine, 2-chloro-2'-deoxyadenosine (Cl-Ado) or ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 39 publications
3
32
0
1
Order By: Relevance
“…Despite showing other markers of capacitation, TALP 3 hC CAP STIM (Table 2) did not display signs of hyperactivation, such as decreased linearity from asymmetrical flagellar beating, high-amplitude head movements (ALH) or increased curvilinear velocity (Kay & Robertson 1998). This correlates with earlier studies in the ram (Colas et al 2010) and bull (Marquez & Suarez 2004) which suggest that hyperactivation is not linked to the cAMP pathway or tyrosine phosphorylation.…”
Section: Pen Can Be Successfully Included In Ram Sperm Capacitation Psupporting
confidence: 79%
“…Despite showing other markers of capacitation, TALP 3 hC CAP STIM (Table 2) did not display signs of hyperactivation, such as decreased linearity from asymmetrical flagellar beating, high-amplitude head movements (ALH) or increased curvilinear velocity (Kay & Robertson 1998). This correlates with earlier studies in the ram (Colas et al 2010) and bull (Marquez & Suarez 2004) which suggest that hyperactivation is not linked to the cAMP pathway or tyrosine phosphorylation.…”
Section: Pen Can Be Successfully Included In Ram Sperm Capacitation Psupporting
confidence: 79%
“…The content of cholesterol in the separated fractions was not significantly different between the control, capacitated and acrosomereacted samples, although the CTC staining was able to discriminate different capacitation patterns in agreement with previous reports [63]. An interesting feature about cholesterol is that, while we were not able to evidence its efflux linked to capacitation in ram spermatozoa [14], the results of this study confirmed a loss of cholesterol from DRMs and non-DRMs fractions in capacitated and acrosome-reacted sperm.…”
Section: Discussionsupporting
confidence: 80%
“…El promedio de ALH para todas las muestras analizadas fue de 4,90 µm. Se considera que el valor lí-mite para espermatozoides hiperactivo en ovinos ha sido previamente establecido con un ALH > 7 µm y una linealidad < 45 % (19). Este hecho no hace referencia a un movimiento hiperactivo, pero sí a un movimiento más amplio que permitiría tener un recorrido mayor en la trayectoria de la célula.…”
Section: Figura 2 Promedio Y Eem Para Las Variables Cinemáticas De Aunclassified